Gold nanourchins and celastrol reorganize the nucleo- and cytoskeleton of glioblastoma cells. Issue 4 (8th January 2018) - Maysinger, Dusica; Moquin, Alexandre; Choi, Jason; Kodiha, Mohamed; Stochaj, Ursula
Abstract : Gold nanourchins (AuNUs) associate with lysosomes and lipid droplets (LDs) in glioblastoma cells. AuNUs reorganize F-actin, microtubules and the nuclear lamina. This alters cell signaling and increases cell death. Cell injury is further enhanced by celastrol. Abstract : The physicochemical properties and cytotoxicity of diverse gold nanoparticle (AuNP) morphologies with smooth surfaces have been examined extensively. Much less is known about AuNPs with irregular surfaces. This study focuses on the effects of gold nanourchins in glioblastoma cells. With limited success of monotherapies for glioblastoma, multimodal treatment has become the preferred regimen. One possible example for such future therapeutic applications is the combination of AuNPs with the natural cytotoxic agent celastrol. Here, we used complementary physical, chemical and biological methods to characterize AuNPs and investigate their impact on glioblastoma cells. Our results show that gold nanourchins altered glioblastoma cell morphology and reorganized the nucleo- and cytoskeleton. These changes were dependent on gold nanourchin surface modification. PEGylated nanourchins had no significant effect on glioblastoma cell morphology or viability, unless they were combined with celastrol. By contrast, CTAB-nanourchins adversely affected the nuclear lamina, microtubules and filamentous actin. These alterations correlated with significant glioblastoma cell death. We identified several mechanisms that contributed to the impact of AuNPs on the cytoskeleton and cell survival. Specifically, CTAB-nanourchins caused a significant increase in the abundance of Rock1. This protein kinase is a key regulator of the cytoskeleton. In addition, CTAB-nanourchins led to a marked decline in pro-survival signaling via the PI3 kinase-Akt pathway. Taken together, our study provides new insights into the molecular pathways and structural components altered by gold nanourchins and their implications for multimodal glioblastoma therapy.